Clinical and histopathological characteristics of primary focal segmental glomerulosclerosis in Turkish adults - Kurultak, İlhan; Güngör, Özkan; Öztürk, Savaş; Dirim, Ahmet Burak; Eren, Necmi; Yenigün, Ezgi; Dal, Elbis Ahbab; Dinçer, Mevlüt Tamer; Bora, Feyza; Akgür, Suat; Sumnu, Abdullah; Dursun, Belda; et al. (Nature Research, 2024)
The data regarding primary FSGS (pFSGS) from different parts of the world differ. While the prevalence of pFSGS has been increasing in Western countries like the USA, it follows an inconsistent trend in Europe and Asia and a decreasing trend in Far Eastern countries such as China in the last two decades. There are undetermined factors to explain those national and geographic discrepancies. Herein, we aimed to reveal the current prevalence with clinical and histopathological characteristics of pFSGS in Turkish adults. This study includes the biopsy-proven pFSGS patients data recorded between 2009 and 2019, obtained from the national multicenter primary glomerulonephritis registry system of the Turkish Society of Nephrology Glomerular Diseases (TSN-GOLD) database. 850 of the 3875 primer glomerulonephritis patients(21.9%) have pFSGS. The mean age is 40.5 ± 14.2 and 435 (51.2%) of patients are male. Nephrotic syndrome is the most common biopsy indication (59.2%). 32.6% of patients have hematuria, 15.2% have leukocyturia and 7.8% have both. Serum creatinine, albumin, and proteinuria are 1.0 mg/dL (IQR = 0.7–1.4) mg/dl, 3.4 ± 0.9 g/dl, 3400 mg/day(IQR, 1774–5740), respectively. Females have lower mean arterial pressure (? 2.2 mmHg), higher eGFR (+ 10.0 mL/min/1.73 m2), and BMI (+ 1.6 kg/m2) than males. Thickened basal membrane(76.6%) and mesangial proliferation (53.5%) on light microscopy are the major findings after segmental sclerosis. IgM (32.7%) and C3 (32.9%) depositions are the most common findings on immunofluorescence microscopy. IgM positivity is related to lower eGFR, serum albumin, and higher proteinuria. The prevalence of pFSGS is stable although slightly increasing in Turkish adults. The characteristics of the patients are similar to those seen in Western countries.
Keywords: FSGS; Histopathological features; Nephrotic syndrome; Primary focal segmental glomerulosclerosis; Turkish adults